Enhancing Teachers’ Pedagogical Quality through STEAM–Heritage Learning: The Dalium Project-Based Learning Syntax for Portfolio-Based Assessment of Science Collaboration, Civic Engagement, and Public Communication - Lubis, Asnarni; Firmansyah, Firmansyah; Lubis, Nazriani; Ferbriansyah, Muhammad; Mahmud, Hafini (Jurnal Pendidikan IPA Indonesia, 2026)
The limited integration of cultural heritage into STEAM education in Indonesia, Malaysia, and Brunei Darussalam has shifted learning practices toward modernization-oriented approaches while weakening students’ cultural identity and civic awareness. Although ASEAN countries possess rich Malay cultural heritage as a distinctive national identity, its preservation in education remains largely confined to arts, performances, and museums rather than being meaningfully integrated into classroom learning. This study aims to develop and empirically validate Dalium Project Learning, a culturally integrated Science, Technology, Engineering, Arts, and Mathematics (STEAM) instructional model designed to strengthen teachers’ pedagogical quality through portfolio-based assessment and heritage-oriented project learning. The study employed a Research and Development approach based on the Analysis, Design, Development, Implementation, and Evaluation framework, involving 48 in-service teachers from Indonesia and Malaysia selected through purposive sampling, supported by qualitative interview data from Brunei Darussalam. Data were analyzed using K-Means Cluster analysis and Two-Way ANOVA with a 2 × 3 factorial design. The findings revealed significant effects of STEAM–Heritage Learning on science collaboration, civic engagement, and public communication, with the highest improvement observed in science collaboration. The study concludes that Dalium Project Learning effectively integrates cultural heritage, collaborative inquiry, and portfolio-based assessment to strengthen pedagogical quality, communication skills, and socially responsive learning environments. The novelty of this study lies in positioning culture as artistic preservation and as a transformative pedagogical foundation that strengthen ASEAN cultural identity amidst the challenges of globalization.